CRISPR/Cas9-mediated disruption of SHANK3 in monkey leads to drug-treatable autism-like symptoms. (16th October 2018) - Tu, Zhuchi; Zhao, Hui; Li, Bang; Yan, Sen; Wang, Lu; Tang, Yongjin; Li, Zhujun; Bai, Dazhang; Li, Caijuan; Lin, Yingqi; Li, Yuefeng; Liu, Jianrong; et al.
Abstract: Monogenic mutations in the SHANK3 gene, which encodes a postsynaptic scaffold protein, play a causative role in autism spectrum disorder (ASD). Although a number of mouse models with Shank3 mutations have been valuable for investigating the pathogenesis of ASD, species-dependent differences in behaviors and brain structures post considerable challenges to use small animals to model ASD and to translate experimental therapeutics to the clinic. We have used clustered regularly interspersed short palindromic repeat/CRISPR-associated nuclease 9 to generate a cynomolgus monkey model by disrupting SHANK3 at exons 6 and 12. Analysis of the live mutant monkey revealed the core behavioral abnormalities of ASD, including impaired social interaction and repetitive behaviors, and reduced brain network activities detected by positron-emission computed tomography (PET). Importantly, these abnormal behaviors and brain activities were alleviated by the antidepressant fluoxetine treatment. Our findings provide the first demonstration that the genetically modified non-human primate can be used for translational research of therapeutics for ASD.